Aetiology, comorbidities and cofactors of chronic leg ulcers: retrospective evaluation of 1 000 patients from 10 specialised dermatological wound care centers in Germany - Jockenhoefer, Finja; Gollnick, Harald; Herberger, Katharina; Isbary, Georg; Renner, Regina; Stuecker, Markus; Valesky, Eva; Wollina, Uwe; Weichenthal, Michael; Karrer, Sigrid; Kuepper, Bernhard; Roesch, Alexander; et al. (International Wound Journal, 2016)
Numerous comorbidities and cofactors have been known to influence wound healing processes. In this multicentre study, clinical data of 1 000 patients with chronic leg ulcers from ten specialised dermatological wound care centers were analysed. The patient cohort comprised 567 females and 433 males with an average age of 69·9 years. The wounds persisted on average for 40·8 months and had a mean size of 43·7 cm(2) . Venous leg ulcers represented the most common entity accounting for 51·3% of all chronic wounds, followed by mixed-type ulcers in 12·9% and arterial ulcerations in 11·0% of the patients. Vasculitis was diagnosed in 4·5%, trauma in 3·2%, pyoderma gangrenosum in 2·8%, lymphoedema in 1·7%, neoplasia in 1·0% and delayed post-surgical wound healing in 0·6% of the included patients. In total, 70·5% of patients suffered from arterial hypertension, 45·2% were obese, 27·2% had non-insulin dependent diabetes, and 24·4% dyslipidaemia. Altogether 18·4% suffered from metabolic syndrome. Cofactors and comorbidities of patients with chronic leg ulcers have previously been studied but not in detail. Here, we were able to demonstrate the existence of several potentially relevant cofactors, comorbidities of their associations and geographical distributions, which should be routinely examined in patients with chronic leg ulcers and - if possible - treated.
EVALuna2:19632